2013
DOI: 10.1021/jm400664x
|View full text |Cite
|
Sign up to set email alerts
|

Heteroaromatic and Aniline Derivatives of Piperidines As Potent Ligands for Vesicular Acetylcholine Transporter

Abstract: To identify suitable lipophilic compounds having high potency and selectivity for vesicular acetylcholine transporter (VAChT), a heteroaromatic ring or a phenyl group was introduced into the carbonyl-containing scaffold for VAChT ligands. Twenty new compounds with ALog D values between 0.53-3.2 were synthesized, and their in vitro binding affinities were assayed. Six of them (19a, 19e, 19g, 19k and 24a-b) displayed high affinity for VAChT (Ki = 0.93 – 18 nM for racemates) and moderate to high selectivity for V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 49 publications
(110 reference statements)
5
51
0
Order By: Relevance
“…The most promising ligands were radiolabeled, and we had performed preliminary evaluation in rodents and NHPs. Among these, (−)-[ 11 C] TZ659 demonstrated favorable initial results during in vivo evaluation in rats and preliminary CNS imaging studies in a male macaque [27, 28]. Here we further demonstrate in vivo binding specificity of (−)-[ 11 C] TZ659 for VAChT in healthy adult male NHPs under physiological conditions (baseline) and different pharmacological challenge conditions.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…The most promising ligands were radiolabeled, and we had performed preliminary evaluation in rodents and NHPs. Among these, (−)-[ 11 C] TZ659 demonstrated favorable initial results during in vivo evaluation in rats and preliminary CNS imaging studies in a male macaque [27, 28]. Here we further demonstrate in vivo binding specificity of (−)-[ 11 C] TZ659 for VAChT in healthy adult male NHPs under physiological conditions (baseline) and different pharmacological challenge conditions.…”
Section: Introductionmentioning
confidence: 64%
“…The synthesis of (−)- TZ659 and the radiolabeling of (−)-[ 11 C] TZ659 were accomplished as previously described [27]. The radiochemical yield was 40–50% (decay corrected to end of bombardment (EOB)) with a radiochemical purity > 99%, the chemical purity of > 95%, and the specific activity was >74 kBq /µmol (decay corrected to EOB).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The epoxide compound 15 was synthesized as previously described. [36, 38] Commercially available (4-fluorophenyl)(piperidin-4-yl)methanone ( 16) was reacted with 15 to afford the phenol regioisomers 17a and 17b . The desired ligands 18a and 18b were obtained via O -alkylation of 17a and 17b respectively with -2-fluoroethyl tosylate.…”
Section: Resultsmentioning
confidence: 99%
“…[35-40] Evaluation of these 11 C- and 18 F-labeled radiotracers in rodents and microPET imaging studies in NHPs suggested that the radiolabeled version of several ligands ( 7-10, Figure 1 ) bound in vivo to the VAChT enriched striatal regions. [38-41] The half-life of 18 F (T 1/2 = 109.8 min) permits longer scan sessions that generate higher target-to-reference ratios; 18 F PET tracers also place fewer time constraints on tracer production. Here we further explore carbonyl-containing benzovesamicol analogues using the following strategies: 1) Incorporating PEGylated groups on the phenyl ring linked to the piperidinyl ring by the carbonyl group ( Figure 1 ), which can improve clearance kinetics by decreasing lipophilicity;[42-44] 2) Introducing a fluoroethoxy group on the tetralin moiety to further improve affinity and selectivity for VAChT versus the σ receptors; 3) Incorporating a fluorine atom to provide position(s) for 18 F radiolabeling.…”
Section: Introductionmentioning
confidence: 99%